2003
DOI: 10.1590/s0102-86502003001200013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and bacterial susceptibility of hospital acquired urinary tract infection

Abstract: PURPOSE: Urinary tract infection is the most common nosocomially acquired infection. It is important to know the etiology and antibiotic susceptibility infectious agents to guide the initial empirical treatment. OBJECTIVE: To determine the prevalence of bacterial strains and their antibiotic susceptibility in nosocomially acquired urinary tract infection in a university hospital between January and June 2003. METHODS: We analyzed the data of 188 patients with positive urine culture (= 10(5) colony-forming unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 10 publications
2
10
0
1
Order By: Relevance
“…29 In this study, E. coli was the most common organism isolated in the culture of the urine sample (68.5%) followed by klebsiella (18.4%), which is in congruence with other studies. 13,[30][31][32][33] This study also showed a lower prevalence of Gram-positive pathogens (0.4%). Contrary to our findings, few other studies have demonstrated a higher proportion of these pathogens ranging up to 26%.…”
Section: Discussionsupporting
confidence: 54%
“…29 In this study, E. coli was the most common organism isolated in the culture of the urine sample (68.5%) followed by klebsiella (18.4%), which is in congruence with other studies. 13,[30][31][32][33] This study also showed a lower prevalence of Gram-positive pathogens (0.4%). Contrary to our findings, few other studies have demonstrated a higher proportion of these pathogens ranging up to 26%.…”
Section: Discussionsupporting
confidence: 54%
“…Since treatment of UTI is frequently started empirically, prior information on the prevalence of causative agents as well as the antimicrobial susceptibility profiles in a particular setting is essential [ 20 ]. However, the distribution of UTI causative agents and their antibiotic susceptibility profiles differs regionally [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antibiotic sensitivity patterns of bacteria isolated from urinary tracts differ for different bacteria and antibiotics [ 6 , 7 , 13 ] with sensitivity to the Quinolones being usual while resistance is often seen to nitrofurantoin; Ampicillin and Cotrimoxazole. So far, E.coli has been reported as the most resistant microorganism almost for all antibiotics including Quinolones [ 6 , 14 ] leading to recurrent infections [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%